Fiscal incentives for improved forest management and deforestation-free agricultural commodities in Central and West Africa - (:unkn) unknown (My University, 2023)
Until recently, little or no use was made of fiscal instruments for forest protection in developing countries. The rise of independent third-party certification systems since the 1990s opens new perspectives for using taxation as an incentive. In the forestry sector, certification has developed significantly in Central Africa but reached a plateau in the last ten years, apparently due to the reorientation of timber export flows towards Asian markets that do not demand certified products. Fiscal incentives, through tax cuts for responsible producers, could compensate for the absence of price premiums but would diminish public revenues. The principle of the "bonus-malus" (feebates) seems promising to the extent that it does not reduce government budgetary revenues (budget neutrality). Bonus-malus schemes can also promote certified "zero deforestation" or "grown in agroforestry" agricultural production, especially cocoa, a significant driver of deforestation in Africa. Governments can select one or several certification schemes, private or public ones, and target fiscal incentives related to these certified products. The peculiarity of a bonus-malus system is that the revenues generated by the malus are expected to decrease progressively (with the adoption of certification), requiring a reduction of the bonus rates in order to respect budget neutrality. Adopting such a scheme would create winners and losers, therefore, complementary policy measures targeting small-scale producers are desirable.
Keywords: African Research